Angiotensin II stimulates melanogenesis via the protein kinase C pathway - LIU, LI-HONG (Exp Ther Med, 2015)
Melanogenesis is a physiological process that results in the synthesis of melanin pigments, which serve a crucial function in hyperpigmentation. The aim of the present study was to determine the effects of angiotensin II (Ang II) on melanogenesis and to elucidate the molecular events of Ang II-induced melanogenesis. Experiments were performed on human melanocytes to elucidate the pigmenting effect of Ang II and the underlying mechanisms. The elements involved in melanogenesis, including melanin content, tyrosinase (TYR) activity, and microphthalmia-associated transcription factor (MITF) and TYR expression at the mRNA and protein levels were evaluated. Melanin content and TYR activity increased in response to Ang II treatment in a concentration-dependent manner. MITF and TYR mRNA and protein expression levels were increased significantly in response to Ang II in a concentration-dependent manner. The Ang II-induced increase in melanin synthesis was reduced significantly in response to co-treatment with Ro-32-0432, a protein kinase C (PKC) inhibitor, whereas co-treatment with H-89, a PKA inhibitor, did not attenuate the Ang II-induced increase in melanin levels. These results suggest that PKC is required for Ang II-induced pigmentation in human melanocytes and that the mechanism involves the PKC pathway and MITF upregulation.